Transnationalism: A Concept of Bridging People and Connecting Nations - T, Abirami; C, Alamelu (International Journal of Psychosocial Rehabilitation, 2020)
Globalisation has influenced people from every corner of the world by connecting people from different nations and has also enabled people to move from one corner of the world to the other effortlessly. This movement of people has empowered the capacity of the people to develop multiple connections with various nations simultaneously. This pattern of multiple connections has attracted the writers to study the movement of immigrants and they framed the terminology as transnationalism. Transnationalism is a global phenomenon which deals with multiple networks created by people from different countries where they accept and adapt to non-native cultures. Various writers have defined transnationalism in their own versions and some researchers have given different interpretations of the concept by comparing it with other concepts. The objective of the present paper is to examine the definition of transnationalism given by various writers and to analyse the different perspectives of the researchers in approaching the concept of transnationalism. It also details the development of the concept of transnationalism from word to an ideology.